Efektivitas Cognitive Behavior Therapy pada Pecandu Narkoba: Systematic Literature Review - Cici Listy Utami; Made Suandika; Fauziah Hanum (LPPM Institut Pendidikan Nusantara Global, 2026)
Drug abuse is a global health issue that affects physical, psychological, and social aspects. In Indonesia, the prevalence of drug abuse remains high, particularly among people of working age. Cognitive Behavioral Therapy (CBT) is an evidence-based psychosocial intervention widely used in the rehabilitation of drug addicts. This study aims to evaluate the effectiveness of cognitive behavioral therapy for drug addicts. A systematic review was conducted in accordance with the PRISMA 2020 guidelines through searches in PubMed, ScienceDirect, and Taylor & Francis from 2015 to 2025. Articles meeting the inclusion criteria were randomized controlled trials (RCTs) assessing the effectiveness of CBT in drug users. Methodological quality was assessed using the Joanna Briggs Institute (JBI) instrument. A total of 9 articles met the inclusion criteria. The synthesis results indicate that CBT is effective in reducing the frequency of drug use, lowering the risk of relapse, and improving psychological symptoms such as depression and anxiety. CBT also enhances patients’ self-efficacy and self-esteem. The combination of CBT with pharmacotherapy yields more optimal results compared to monotherapy. CBT is an effective intervention in drug addiction rehabilitation as it reduces substance use and improves psychological well-being. CBT is recommended as an evidence-based approach in addiction rehabilitation services.